Iron-based phosphate or fluorophosphate polyanionic compound as well as preparation and application thereof

By adding high thermal conductivity additives to the precursor of phosphate or fluorophosphate polyanionic materials and performing airflow pulverization, the problem of uneven thermal effects in phase formation reactions is solved, and high-purity and high-performance materials are prepared. Improve the performance of the positive electrode material of sodium ion battery.

CN119284853APending Publication Date: 2025-01-10DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310837167.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When preparing phosphate or fluorophosphate polyanionic materials, uneven thermal effects in the phase formation reaction lead to uneven sintering, affecting the purity and circulation stability of the product.

Method used

Add high thermal conductivity additives such as acetylene black, carbon black, graphite, etc. to the precursor powder to reduce heat accumulation, improve uniformity of the heat treatment process, and remove thermal conductivity additives through airflow pulverization to prepare high purity, high specific capacity, and high Materials with cycle stability.

Benefits of technology

It effectively avoids uneven growth of crystals inside and outside during heat treatment, improves the electrochemical performance and rate performance of the material, promotes the application of the positive electrode material of sodium ion battery, and improves the development of energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284853A_ABST
    Figure CN119284853A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium-ion battery electrode material, in particular to a preparation method of a phosphate or fluorophosphate polyanionic compound and application of the phosphate or fluorophosphate polyanionic compound in the sodium-ion battery electrode material. The iron-based phosphate polyanionic compound has one or more than two of the structures as shown in a formula I, a formula II, a formula III, a formula IV or a formula V and a formula VI: Na4Fe3 (PO4) 2P2O7, Na3Fe2 (PO4) 1P2O7, NaFePO4, Na2FeP2O7, Na2FePO4F and Na5Fe2 (PO4) 2F3; the prepared phosphate and fluorophosphate polyanionic compound particles are small in particle size and uniform in distribution, and the product is high in purity and has good electrochemical performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion batteries and relates to sodium ion battery electrode materials, in particular to a preparation method of phosphate or fluorophosphate polyanionic compounds and application of the same in sodium ion battery electrode materials. Background Art

[0002] In recent years, as the key to regulating the volatility and indirectness of new energy and achieving grid stability, the energy storage industry has always maintained a high level of attention, and alkali metal (Li, Na, K) ion batteries are an important component of portable large-scale fixed energy storage. Among them, lithium-ion batteries (LIBs) are widely used in electric vehicles and electronic devices due to their significant advantages such as high energy density, high electrode potential, stable cycle performance and environmental friendliness. However, in recent years, the problem of lithium source limitation has led to high prices for lithium-ion battery cathode materials. Sodium-ion batteries have a similar working principle to lithium-ion batteries, and sodium sources are low in cost and abundant in resources. Therefore, it is particularly important to develop sodium-ion battery cathode materials with excellent performance.

[0003] Polyanionic materials such as sodium iron phosphate, sodium iron pyrophosphate, sodium iron fluorophosphate, and sodium iron phosphate pyrophosphate have become the preferred positive electrode materials for alkali metal ion batteries due to their stable structure and high safety. In the production process of phosphate and fluorophosphate polyanionic materials, the precursors are mixed by ball milling or sand milling, and then dried to obtain the precursors, which are then calcined at high temperature to form phases. However, in the phase formation reaction, the phase formation mechanism, thermal effect, thermal conductivity and heat storage coefficient of the intermediates of different types of precursors are different, which greatly affects the uniformity of the heat treatment reaction in the phase formation process, such as a series of problems such as agglomeration and hardening, which makes the material sintered unevenly inside and outside; when the mass of the precursor increases, the above-mentioned reaction thermal effect aggravates the influence of the uniformity of the reaction and product during the heat treatment process, thereby affecting the purity of the product, and also has a great impact on the rate performance and cycle stability of the product. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method that can effectively alleviate the problem of uneven sintering caused by the above thermal effect. By adding an additive material with a high thermal conductivity coefficient (such as one or more of acetylene black, carbon black, Ketjen black, graphite, carbon nanotubes, carbon fiber, and graphene) to the precursor powder, the heat accumulation in the precursor phase formation process is effectively reduced, and the influence on the uniformity of the overall heat treatment process is improved; the introduction of the above technology can still prepare phosphate and fluorophosphate polyanionic materials with high purity, high specific capacity, high rate performance, and high cycle stability even when the mass of the precursor increases, which greatly promotes the development and application of such materials in the field of energy storage.

[0005] A method for preparing an iron-based phosphate or fluorophosphate polyanionic compound,

[0006] The compound has one or more structures shown in the following iron-based phosphate polyanion compound formula I, formula II, formula III, formula IV, or fluorophosphate polyanion compound formula V, or formula VI:

[0007] Na4Fe3(PO4)2P2O7 Formula Ⅰ;

[0008] Na3Fe2(PO4)1P2O7 Formula II;

[0009] NaFePO4 formula III;

[0010] Na2FeP2O7 Formula IV;

[0011] Alternatively, the iron-based fluorophosphate polyanionic compound has a structure shown in Formula V and / or VI:

[0012] Na2FePO4 F Formula V;

[0013] Na5Fe2(PO4)2F3 Formula VI;

[0014] The preparation method of the polyanionic compound shown in Formula I, Formula II, Formula III, Formula IV, V or VI comprises:

[0015] Step 1, mixing a carbon source, a sodium source, an iron source, a phosphorus source, and an additive raw material in a solvent to obtain a precursor slurry, or mixing a carbon source, a sodium source, an iron source, a phosphorus source, a fluorine source, and an additive raw material in a solvent to obtain a precursor slurry, and drying to obtain a precursor powder;

[0016] The additive raw material is one or more of acetylene black, carbon black, Ketjen black, graphite, carbon nanotubes, carbon fiber, and graphene; the added mass M1 of the additive raw material is 0.5% to 10% of the total mass of the compound material synthesis raw material described in step 1 (the compound material synthesis raw material includes the mass sum of the added carbon source, sodium source, iron source, and phosphorus source, or the compound material synthesis raw material includes the mass sum of the added carbon source, sodium source, iron source, phosphorus source, and fluorine source); more preferably 4% to 6%;

[0017] The particle size range of the precursor slurry is 0.3 μm-1.5 μm;

[0018] Step 2, heat-treating the precursor powder obtained in step 1 in an inert atmosphere or an inert atmosphere containing H2, and obtaining a product M2 of an iron-based phosphate or fluorophosphate polyanionic compound after the heat treatment;

[0019] The heat treatment atmosphere is selected from an inert atmosphere or an inert atmosphere containing reducing H2, and the molar content of H2 in the heat treatment atmosphere is 0-50%, preferably 10%-20%; the heat treatment includes a process of treating at a first temperature T1 and a process of treating at a second temperature T2 after the treatment at the first temperature T1; the temperature T1 is 200≤T1≤400°C, and the treatment time is 0.5-6 h; the temperature T2 is 400°C<T1≤650°C, and the treatment time is 3-20 h; the difference between T2 and T1 is greater than or equal to 50°C;

[0020] Step 3: Remove the additive raw materials added in Step 1 from the product obtained in Step 2 by a jet mill to obtain the final product M3 of the iron-based phosphate or fluorophosphate polyanionic compound. The particle size range of the final product is 0.2 μm-5 μm, and the preferred range is 1.5 μm-3.5 μm. The yield before and after jet milling (the yield is defined as: the mass ratio of the final product powder material obtained after jet milling to the mass of the substance excluding the additive raw materials added in Step 1 in the product obtained after heat treatment in Step 2, that is, M3 / (M2-M1)) is 60%-85%, and the preferred range is 75%-80%;

[0021] The iron-based phosphate polyanionic compound is a carbon-coated iron-based phosphate polyanionic compound material, and the addition amount of the carbon source should ensure that the mass content of carbon in the phosphate or fluorophosphate polyanionic compound after jet milling is 3 wt%-10 wt%, and further preferably 4 wt%-5 wt%.

[0022] In Step 1, when the additive raw material contains acetylene black, carbon black, Ketjen black or graphite, its particle size is 10 nm-200 nm, and further preferably 50-100 nm;

[0023] When the additive raw material contains carbon nanotubes or carbon fibers, its diameter distribution is 2 nm-20 nm, and further preferably 5-10 nm;

[0024] When the additive raw material contains graphene, its thickness is 0.3 nm-3.5 nm, and further preferably 1-2 nm;

[0025] In Step 1, there are no other insoluble particulates in the uniformly mixed precursor slurry except the additive raw materials (that is, the added carbon source, sodium source, iron source, and phosphorus source are all soluble compounds, or the added carbon source, sodium source, iron source, phosphorus source, and fluorine source are all soluble compounds), or when there are other insoluble particulates in the uniformly mixed precursor slurry except the additive raw materials;

[0026] In Step 2, the inert atmosphere gas includes at least one or more of argon, helium, and nitrogen.

[0027] In step 1, the sodium source, iron source, phosphorus source, and additive raw materials are uniformly mixed in a solvent by at least one or more of ball milling, pot milling, sand milling, etc.; the solvent is water, ethanol, or a mixed solvent of water and ethanol, and the solid content of the precursor solution is 30wt% to 75wt%, more preferably 45wt% to 55wt%:

[0028] The sand milling process requires the addition of a sand milling medium, the sand milling speed is 2000-5000 r / min, and the sand milling time is 0.5-8 h; the sand milling medium is one or more of natural sand beads, glass beads, steel beads, zirconium oxide beads, zirconium silicate beads, and agate beads; the ball-to-material ratio (mass ratio of balls (medium) to solid materials (other substances except solvents)) is (1-10); the diameter of the sand milling medium is 0.2-1 cm, and is preferably composed of 0.4 cm and 0.6 cm in diameter according to a mass ratio of 2:1;

[0029] The ball mill needs to add ball milling media, the rotation speed of the ball mill is 200-800r / min, and the ball milling treatment time is 3-15h; the ball milling media is one or more of zirconium oxide beads, agate beads, zirconium silicate beads, etc.; the ball-to-material ratio (mass ratio of balls (medium) to solid materials (other substances except solvent)) is (1.5-7); the diameter of the ball milling media is 2-12cm, preferably composed of diameters of 6cm, 4cm, and 2cm in a mass ratio of 1:2:2;

[0030] The pot mill needs to be added with pot mill media. The rotation speed of the pot mill in step 1 is 20-40 r / min, and the pot mill treatment time is 20h-72h.

[0031] The pot mill medium is one or more of zirconium oxide beads, agate beads, and zirconium silicate beads; the ball-to-material ratio (mass ratio of balls (medium) to solid materials (other substances except solvent)) is (1.1-3); the diameter of the pot mill medium is 4-12 cm, preferably a combination of 6 cm and 4 cm in diameter according to a mass ratio of 2:1;

[0032] The solvent is water, ethanol, or a mixed solvent of water and ethanol. The mass of water in the mixed solvent preferably accounts for (30-80) wt%, more preferably (45-55) wt%, and the mass of ethanol preferably accounts for (20-70) wt%, more preferably (45-55) wt%.

[0033] The drying method in step 1 is preferably spray drying. Preferably, the feed flow rate is controlled to be 20mL / min~60mL / min, the inlet air temperature is controlled to be 120℃~195℃, the exhaust port temperature is 80℃~110℃, the compressed air pressure is 0.03KPa~0.9KPa, and the precursor slurry is pumped into the spray dryer atomizer through a peristaltic pump to collect the powder; after the precursor slurry is dried, a precursor powder with a particle size of 20μm-30μm is obtained.

[0034] The air flow mill described in step 3 is a fluidized bed air flow mill (with a turbine classifier), a circulating tubular air flow mill (with an inertial classifier) ​​or a jet air flow mill (with a classifying wheel belt). The compressed air pressure is 4 to 12 MPa. Sampling inspection is carried out every 1-20 minutes (preferably 5-15 minutes) to detect whether the additive raw materials are present in the materials collected after air flow milling. The inspection time when the additive raw materials are just completely removed is the air flow milling time. Usually, the air flow milling time is 1h-5h.

[0035] 1) The iron source is selected from one or more of iron powder, ferrosinite, ferrous oxide, ferrous oxalate, ferrous oxalate (dihydrate), ferric phosphate, ferric pyrophosphate, ferrous citrate, ferric nitrate, ferrous nitrate, ferrous sulfate, ferrous sulfate, ferrous chloride, ferrous chloride, ferrous acetate, ammonium ferrous sulfate, ferric citrate, ammonium ferric citrate, and sodium ferric citrate succinate;

[0036] 2) The sodium source is at least one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium phosphate, sodium pyrophosphate, sodium hydrogen pyrophosphate, sodium hydrogen phosphate, sodium dihydrogen phosphate, sodium citrate, sodium oxalate, sodium nitrate, sodium tartrate, sodium ascorbate, sodium gluconate, sodium glutamate, and sodium formate;

[0037] 3) The phosphorus source is at least one or two or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid, ammonium dihydrogen phosphate, triammonium phosphate, pyrophosphoric acid, sodium pyrophosphate, sodium dihydrogen pyrophosphate, and ammonium dihydrogen pyrophosphate;

[0038] 4) The carbon source is selected from at least one or more of starch, carboxymethyl starch, sodium carboxymethyl starch, sodium alginate, citric acid, oxalic acid, ammonium citrate, ascorbic acid, formaldehyde, acetaldehyde, lactic acid, malic acid, glucose, sucrose, maltose, and maltodextrin;

[0039] 5) The fluorine source is selected from at least one or more of sodium fluoride, ammonium fluoride, polyvinylidene fluoride, polyperfluoroethylene, and hydrofluoric acid.

[0040] Preferably, the phosphate polyanionic compound has a structure as shown in formula I, and in the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 4:3:4, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively;

[0041] Preferably, the phosphate polyanionic compound has a structure as shown in Formula II. In the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 3:2:3, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively;

[0042] Preferably, the polyanionic compound has a structure as shown in Formula III, and in the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 1:1:1, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively;

[0043] Preferably, the polyanionic compound has a structure as shown in Formula IV. In the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 2:1:2, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively;

[0044] Preferably, the polyanionic compound has a structure shown in Formula V. In the slurry, the molar ratio of the sodium source, the iron source, the phosphorus source, and the fluorine source is 2:1:1:1, and the molar ratio of the sodium source, the iron source, the phosphorus source, and the fluorine source is based on the molar amount of the sodium element, the iron element, the phosphorus element, and the fluorine element, respectively;

[0045] Preferably, the polyanionic compound has a structure as shown in VI. In the slurry, the molar ratio of the sodium source, iron source, phosphorus source and fluorine source is 5:2:2:3, and the molar ratio of the sodium source, iron source, phosphorus source and fluorine source is based on the molar amount of the sodium element, iron element, phosphorus element and fluorine element, respectively.

[0046] The iron-based phosphate or fluorophosphate polyanionic compound prepared by the preparation method. The use of one or more of the iron-based phosphate or fluorophosphate polyanionic compounds prepared by the preparation method or one or more of the iron-based phosphate or fluorophosphate polyanionic compounds according to claim 8 in sodium ion batteries is characterized in that the one or more of the iron-based phosphate or fluorophosphate polyanionic compounds are used as active substances for positive electrode materials of sodium ion batteries.

[0047] One or more of the iron-based phosphate or fluorophosphate polyanionic compounds prepared by the preparation method or one or more of the iron-based phosphate or fluorophosphate polyanionic compounds;

[0048] In the positive electrode material, the content of the iron-based phosphate or fluorophosphate polyanionic compound is (60-98) wt%;

[0049] The positive electrode material further contains a conductive agent and a binder, wherein the mass ratio of the iron-based phosphate or fluorophosphate polyanionic compound, the conductive agent and the binder is (60-98) wt%: (1-39) wt%: (1-39) wt%;

[0050] The conductive agent is at least one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene;

[0051] The binder is polyvinylidene fluoride: at least one or more of PVDF5130, HSV900 and kynar761A.

[0052] The prepared phosphate and fluorophosphate polyanion compound particles have small particle sizes and are evenly distributed, and the product has high purity and good electrochemical properties and rate performance.

[0053] Beneficial Effects

[0054] Thermal conductivity additives are additive materials with high thermal conductivity, such as one or more of acetylene black, carbon black, Ketjen black, graphite, carbon nanotubes, carbon fiber, and graphene. Thermal conductivity additives are added in the form of raw materials, and are stable and non-decomposed before and after heat treatment. The powder collected after heat treatment is tested for thermal storage coefficient (the thermal storage coefficient refers to a single material layer with sufficient thickness. When one side is subjected to harmonic heat, the surface temperature of the side will fluctuate in the same period. The ratio of the heat flow amplitude through the side surface to the temperature amplitude of the side surface is the thermal storage coefficient of the material. Its value depends on the thermal conductivity, specific heat, bulk density and heat flow fluctuation period of the material. The unit is W / (m 2 K), the larger the heat storage coefficient, the smaller the fluctuation, the better the thermal stability, and the slower the reaction), the addition of the thermal conductive additive raw material reduces the heat storage coefficient of the product and the thermal conductive additive composite material, effectively avoiding the internal heat accumulation during the growth of the crystal from the inside to the outside during the heat treatment process, and improving the uniformity of the heat distribution. It can prepare phosphate and fluorophosphate polyanionic materials with high purity, high specific capacity, high rate performance, and high cycle stability, which greatly promotes the development and application of such materials in the field of energy storage.

[0055] The thermal conductive additive in the product can be effectively removed by the air flow pulverizing device, avoiding the problem of the thermal conductive additive being electrochemically inert during the charge and discharge process and reducing the gram capacity of the material. The product and the thermal conductive additive are separated according to the density difference. Compared with the product, the thermal conductive additive has a smaller density and a smaller inertial force during the air flow pulverizing process. During the air flow pulverizing process, the thermal conductive additive is carried into the cyclone separator or dust collector by the air flow before the product and separated from the product. The diffraction peaks of the thermal conductive additive in the material collected after the air flow pulverizing are sampled and inspected in combination with the XRD detection technology. Based on this, the parameters of the air flow pulverizing device are adjusted to obtain a product with a smaller particle size and a uniform distribution, which effectively improves the exposure of the electrochemical sites of the material during the electrochemical charge and discharge process and maximizes the electrochemical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 is the XRD diffraction spectrum of material 1# in Example 1;

[0057] Figure 2 is the SEM image of material 1# in Example 1;

[0058] Figure 3 is the TEM image of material 1# in Example 1;

[0059] Figure 4 This is the TG curve of material 1# in Example 1. DETAILED DESCRIPTION

[0060] Example 1 Additive raw materials and (the added carbon source, sodium source, iron source, phosphorus source mass and) 5%

[0061] Step 1) 30.19g of iron phosphate FePO4, 18g of ferrous oxalate dihydrate FeC2O4.2H2O, 28.4g of disodium hydrogen phosphate, and 17.4g of starch were weighed and added to 94g of deionized water to form a precursor solution, and 4.68g of additive raw material carbon black (primary particle size: 70nm-75nm) was added to the solution, and transferred to a sand mill with a grinding chamber of 0.3L, and the ball-to-material ratio (mass ratio, ball-to-solid material ratio) was about 8:1 (590g and 187g of zirconium dioxide balls with diameters of 4mm and 6mm were added respectively); the sand mill speed was set to 2000r / min, the time was 6h, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.5μm-0.7μm; (the upper and lower limits of the three tests were respectively taken as the average values ​​of each, the same below);

[0062] Step 2) The sand-milled precursor solution is transferred to a beaker, and then passed into a spray drying device for spray drying (inlet temperature is 170° C., outlet temperature is 100° C., feed flow rate is 50 ml / min, compressed air pressure is 0.8 KPa), to obtain a precursor powder, wherein the particle size of the precursor powder is 20 μm-25 μm;

[0063] Step 3) The precursor powder obtained in step 2) is heat-treated in nitrogen at temperatures T1 and T2 in turn, wherein the T1 heat treatment temperature is 300°C, the heat treatment time is 3h, and the heating rate from room temperature to T1 is 5°C / min; the T2 heat treatment temperature is 500°C, the heat treatment time is 8h, and the heating rate from T1 to T2 is 2°C / min. The sample after heat treatment is a fluffy powder. The collected powder is tested for thermal storage coefficient and recorded in Table 1. An XRD test is performed, and it can be observed that the powder contains 92% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% carbon black (primary particle size: 70nm-75nm) material, and no other impurity phases are present;

[0064] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation effects). Sampling inspection is carried out at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peaks of the additive raw materials in the materials collected after air flow pulverization. The parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7 MPa, and the time reaches 2 h, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization. 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4). At this time, the yield of the target product sodium ferric phosphate pyrophosphate material is 78%, and the removal rate of carbon black is 100%, recorded as sample 1#;

[0065] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample 1#. Figure 1 ) It can be seen that the synthesized material is pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.5. From SEM ( Figure 2 ) It can be seen that the particle size is uniform and small, with a particle size of 1μm-2μm. From TEM ( Figure 3 ) shows that there is an amorphous carbon layer covering the outer surface of the material, with a thickness of about 5 to 6 nm. TG( Figure 4 ) shows that the amorphous carbon content of the material surface coating is 4.8wt%.

[0066] Example 2 Additive raw materials and (the mass of the added carbon source, sodium source, iron source, and phosphorus source) 0.5% The method of Example 1 was used to prepare Na4Fe3(PO4)2P2O7 material. The process and conditions were the same as those of Example 1. The difference from Example 1 was that:

[0067] In step 1), the mass of carbon black (primary particle size: 70nm-75nm) is 0.5g, and the particle size of the precursor slurry is tested by a laser particle size analyzer, and the particle size range is 0.6μm-0.8μm (the upper and lower limits of the test are tested three times and the average values ​​are taken respectively);

[0068] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 94.9% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 1% carbon black (primary particle size: 70nm-75nm) material in the powder, and there are 3.3% M-phase sodium iron phosphate NaFePO4 impurities and 1.6% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases exist;

[0069] Step 4) The powder obtained above is subjected to air flow milling using a fluidized bed air flow mill with a classifying wheel (with both air flow milling and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 8 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow milling, and the parameters of the air flow milling device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 5 MPa, and the time reaches 1.8 h, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow milling. The 1% carbon black (primary particle size: 70 nm-75 nm) material in step 3) can be effectively removed by the air flow milling separation process in step 4), and the target product sodium ferric phosphate pyrophosphate material yield is 85%, and the carbon black removal rate is 100%, recorded as sample 2#;

[0070] Step 5) The prepared sample 2# is characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material contains sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of 95%. There are also 3.35% M-phase sodium iron phosphate NaFePO4 impurities and 1.65% sodium iron pyrophosphate Na2FeP2O7 impurities. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 2μm-5μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 8-9nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 5.0wt%.

[0071] Example 3 Additive raw materials and (the sum of the added carbon source, sodium source, iron source, and phosphorus source) 2.5%

[0072] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0073] The mass of carbon black (primary particle size: 70nm-75nm) in step 1) is 2.34g. The particle size of the precursor slurry is tested by a laser particle size analyzer, and the particle size range is 0.62μm-0.82μm;

[0074] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 93.5% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 4.9% carbon black (primary particle size: 70nm-75nm) material in the powder, and there are 1.1% M-phase sodium iron phosphate NaFePO4 impurities and 0.5% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases exist;

[0075] Step 4) The powder obtained above is subjected to air flow milling using a fluidized bed air flow mill with a classifying wheel (with both air flow milling and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 5 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow milling, and the parameters of the air flow milling device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 6.5 MPa, and the time reaches 1.8 h, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow milling, that is, 4.9% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow milling separation process in step 4), and the target product sodium ferric phosphate pyrophosphate material yield is 81%, and the carbon black removal rate is 100%, recorded as sample 3#;

[0076] Step 5) The prepared sample 3# is characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material contains sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of 98.37%. There are also 1.1% M-phase sodium iron phosphate NaFePO4 impurities and 0.53% sodium iron pyrophosphate Na2FeP2O7 impurities. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 2μm-4μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 7-8nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.9wt%.

[0077] Example 4 Additive raw materials and (the added carbon source, sodium source, iron source, phosphorus source mass sum) 4%

[0078] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0079] The mass of carbon black (primary particle size: 70nm-75nm) in step 1) is 3.744g. The particle size of the precursor slurry is tested by a laser particle size analyzer, and the particle size range is 0.55μm-0.75μm;

[0080] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 92.5% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 7.5% carbon black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases exist;

[0081] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 6.5 MPa, and the time reaches 2 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 7.5% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and the yield of the target product sodium iron phosphate pyrophosphate material is 78.5%, and the removal rate of carbon black is 100%, recorded as sample 4#;

[0082] Step 5) The prepared sample 4# was characterized by XRD, SEM, TEM and carbon content (TG) test. From XRD, it can be seen that the synthesized material is sodium iron pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of 99.2% and no other impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 1.5μm-3μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 6-7nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.85wt%.

[0083] Example 5 Additive raw materials and (the sum of the added carbon source, sodium source, iron source, and phosphorus source) 6%

[0084] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0085] The mass of carbon black (primary particle size: 70nm-75nm) in step 1) is 5.616g. The particle size of the precursor slurry is tested by a laser particle size analyzer, and the particle size range is 0.5μm-0.75μm;

[0086] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 89% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 11% carbon black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases exist;

[0087] Step 4) The powder obtained above is subjected to airflow pulverization using a fluidized bed airflow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both airflow pulverization and separation effects), and a sampling inspection is performed at intervals of 10 minutes by XRD detection technology, and the XRD diffraction peak of the thermal conductive additive in the material collected after airflow pulverization is detected, and the parameters of the airflow pulverization device are adjusted based on this, and the parameters of the airflow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 6.5 MPa, and the time reaches 2.4 h, there are no other impurity phases in the material obtained by airflow pulverization, and there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm), that is, 11% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the airflow pulverization separation process in step 4), and the target product sodium ferric phosphate pyrophosphate material yield is 76.5%, and the removal rate of carbon black is 100%, recorded as sample 5#;

[0088] Step 5) The prepared sample 5# was characterized by XRD, SEM, TEM and the carbon content (TG) was tested. From XRD, it can be seen that the synthesized material is sodium iron pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of 99.4%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.5μm-2μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 4-5nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.65wt%.

[0089] Example 6 Additive raw materials and (the sum of the added carbon source, sodium source, iron source, and phosphorus source) 7.5%

[0090] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0091] The mass of carbon black (primary particle size: 70nm-75nm) in step 1) is 7.02g. The particle size of the precursor slurry is tested by a laser particle size analyzer, and the particle size range is 0.58μm-0.78μm;

[0092] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 87% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 13% carbon black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases exist;

[0093] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7 MPa, and the time reaches 3 hours, there is no carbon black (primary particle size: 70 nm-75 nm) diffraction peak in the material obtained by air flow pulverization, that is, 13% of the carbon black (primary particle size: 70 nm-75 nm) material in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the target product sodium ferric phosphate pyrophosphate material yield is 70%, and the carbon black removal rate is 100%, recorded as sample 6#;

[0094] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample 6#. From XRD, it can be seen that the synthesized material is pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.5%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.5μm-2μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 3-4nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.5wt%. Example 7 Additive raw materials and (the mass of the added carbon source, sodium source, iron source, and phosphorus source) 10%

[0095] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0096] The mass of carbon black (primary particle size: 70nm-75nm) in step 1) is 9.36g. The particle size of the precursor slurry is tested by a laser particle size analyzer, and the particle size range is 0.61μm-0.81μm; (the average value is taken after three tests);

[0097] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 83% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 17% carbon black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases exist;

[0098] Step 4) The powder obtained above is subjected to air flow milling using a fluidized bed air flow mill with a classifying wheel (with both air flow milling and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow milling, and the parameters of the air flow milling device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 8 MPa, and the time reaches 4 hours, there is no carbon black (primary particle size: 70 nm-75 nm) diffraction peak in the material obtained by air flow milling, that is, 17% of the carbon black (primary particle size: 70 nm-75 nm) material in step 3) can be effectively removed by the air flow milling treatment in step 4), and at this time, the target product sodium ferric phosphate pyrophosphate material yield is 60%, and the carbon black removal rate is 100%, recorded as sample 7#;

[0099] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample 7#. From XRD, it can be seen that the synthesized material is pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.7%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.5μm-1.5μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 3-4nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.0wt%. Example 8 The primary particle size of the additive raw material carbon black is 10nm-15nm

[0100] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0101] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 10 nm-15 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.4 μm-0.5 μm;

[0102] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 92.1% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 7.9% carbon black (primary particle size: 10nm-15nm) material in the powder, and no other impurity phases exist;

[0103] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 12 MPa, and the time reaches 5 hours, there is no diffraction peak of carbon black (primary particle size: 10 nm-15 nm) in the material obtained by air flow pulverization, that is, 7.9% of the carbon black (primary particle size: 10 nm-15 nm) material in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 60%, and the removal rate of carbon black is 100%, recorded as sample 8#;

[0104] Step 5) The prepared sample 8# was characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.2μm-1μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 2 to 3nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 3.5wt%.

[0105] Example 9 The primary particle size of the additive raw material carbon black is 50nm-55nm

[0106] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0107] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 50 nm-55 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.45 μm-0.65 μm; (the average value was taken after three tests);

[0108] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 92.05% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 7.95% carbon black (primary particle size: 50nm-55nm) material in the powder, and no other impurity phases exist;

[0109] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 10 MPa, and the time reaches 3.5 h, there is no diffraction peak of carbon black (primary particle size: 50 nm-55 nm) in the material obtained by air flow pulverization, that is, 7.95% of the carbon black (primary particle size: 50 nm-55 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 65%, and the removal rate of carbon black is 100%, recorded as sample 9#;

[0110] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample 9#. From XRD, it can be seen that the synthesized material is pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.1%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.5μm-1.0μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 2 to 3nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 3.7wt%. Example 10 The primary particle size of the additive raw material carbon black is 100nm-105nm

[0111] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0112] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 100 nm-105 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.6 μm-0.8 μm; (the average value was taken after three tests);

[0113] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 91% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% carbon black (primary particle size: 100nm-105nm) material in the powder, and there are 0.6% M-phase sodium iron phosphate NaFePO4 impurities and 0.4% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases exist;

[0114] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are deployed based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 5.5 MPa, and the time reaches 1.8 h, there is no diffraction peak of carbon black (primary particle size: 100 nm-105 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 100 nm-105 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 80%, and the removal rate of carbon black is 100%, recorded as sample 10#;

[0115] Step 5) The prepared sample 10# was characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 98.9%. There are also 0.65% M-phase sodium iron phosphate NaFePO4 impurities and 0.35% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 2μm-3μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 6-7nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.4wt%.

[0116] Example 11 The primary particle size of the additive raw material carbon black is 190nm-200nm

[0117] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0118] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 190 nm-200 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.75 μm-0.95 μm;

[0119] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 90.4% of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8.1% of carbon black (primary particle size: 190nm-200nm) material in the powder, and there are 1% of M-phase sodium iron phosphate NaFePO4 impurities and 0.5% of sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases exist;

[0120] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 5 MPa, and the time is 1.8 h, there is no diffraction peak of carbon black (primary particle size: 190 nm-200 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 190 nm-200 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium ferric phosphate pyrophosphate material is 82%, and the removal rate of carbon black is 100%, recorded as sample 11#;

[0121] Step 5) The prepared sample 11# was characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 98.4%. There are also 1.1% M-phase sodium iron phosphate NaFePO4 impurities and 0.5% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 2.5μm-3.5μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 6-7nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.6wt%.

[0122] Example 12 The particle size range of the precursor slurry particles is 0.3 μm-0.4 μm

[0123] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0124] Step 1) setting the sand milling speed to 5000 r / min for 8 h, and testing the particle size of the precursor slurry by a laser particle size analyzer, the particle size range is 0.3 μm-0.4 μm;

[0125] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 92% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% carbon black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases exist;

[0126] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 10 MPa, and the time is 4 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and the yield of the target product sodium iron phosphate pyrophosphate material is 62%, and the removal rate of carbon black is 100%, recorded as sample 12#;

[0127] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample 12#. From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.5%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.5μm-1μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 2 to 3nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 3.1wt%. Example 13 The particle size range of the precursor slurry particles is 1.4μm-1.5μm

[0128] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0129] Step 1) setting the sand milling speed to 2000 r / min and the time to 1 h, and testing the particle size of the precursor slurry by a laser particle size analyzer, the particle size range is 1.4 μm-1.5 μm;

[0130] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 90% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% carbon black (primary particle size: 70nm-75nm) material in the powder, and there are 1.4% M-phase sodium iron phosphate NaFePO4 impurities and 0.6% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases exist;

[0131] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7 MPa, and the time reaches 2 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 79%, and the removal rate of carbon black is 100%, recorded as sample 13#;

[0132] Step 5) The prepared sample 13# was characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 97.8%. There are also 1.5% M-phase sodium iron phosphate NaFePO4 impurities and 0.7% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-4μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 4-5nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.6wt%.

[0133] Example 14 Heat treatment T2 temperature is 400°C

[0134] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0135] Step 3) The precursor powder obtained in step 2) is heat-treated in nitrogen at temperatures T1 and T2 in turn, wherein the T1 heat treatment temperature is 300°C, the heat treatment time is 3h, and the heating rate from room temperature to T1 is 5°C / min; the T2 heat treatment temperature is 400°C, the heat treatment time is 8h, and the heating rate from T1 to T2 is 2°C / min. The sample after heat treatment is a fluffy powder. The collected powder is tested for thermal storage coefficient and recorded in Table 1. An XRD test is performed, and it can be observed that the powder contains 92% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% carbon black (primary particle size: 70nm-75nm) material, and no other impurity phases are present;

[0136] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill with a classifying wheel (with both air flow pulverization and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7 MPa, and the time reaches 2 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 78%, and the removal rate of carbon black is 100%, recorded as sample 14#;

[0137] Step 5) The prepared sample 14# was characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.5%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.5μm-1.5μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 6 to 7nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 5.0wt%.

[0138] Example 15 Heat treatment T2 temperature is 650°C

[0139] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0140] Step 3) The precursor powder obtained in step 2) is heat-treated in nitrogen at temperatures T1 and T2 in turn, wherein the T1 heat treatment temperature is 300°C, the heat treatment time is 3h, and the heating rate from room temperature to T1 is 5°C / min; the T2 heat treatment temperature is 650°C, the heat treatment time is 8h, and the heating rate from T1 to T2 is 2°C / min. The sample after heat treatment is a fluffy powder. The collected powder is tested for thermal storage coefficient and recorded in Table 1. An XRD test is performed, and it can be observed that the powder contains 88% of sodium iron pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% of carbon black (primary particle size: 70nm-75nm) material, 2.65% of M-phase sodium iron phosphate NaFePO4 impurities and 1.35% of sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases exist;

[0141] Step 4) The powder obtained above is subjected to air flow milling using a fluidized bed air flow mill with a classifying wheel (having both air flow milling and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow milling, and the parameters of the air flow milling device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7.5 MPa, and the time is 2.8 h, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow milling, that is, 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow milling separation process in step 4), and at this time, the yield of the target product sodium ferric phosphate pyrophosphate material is 74%, and the removal rate of carbon black is 100%, recorded as sample 15#;

[0142] Step 5) The prepared sample 15# was characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 95.7%. There are also 2.9% M-phase sodium iron phosphate NaFePO4 impurities and 1.4% sodium iron pyrophosphate Na2FeP2O7 impurities, and no other impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-4μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 3 to 5nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.3wt%.

[0143] Example 16 The additive raw material is acetylene black, and the added amount (the added carbon source, sodium source, iron source, and phosphorus source mass sum) is 4%

[0144] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0145] Step 1) 3.72 g of additive raw material acetylene black (primary particle size: 60 nm-65 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.55 μm-0.75 μm;

[0146] Step 3) The precursor powder obtained in step 2) is heat-treated in nitrogen at temperatures T1 and T2 in turn, wherein the T1 heat treatment temperature is 300°C, the heat treatment time is 3h, and the heating rate from room temperature to T1 is 5°C / min; the T2 heat treatment temperature is 500°C, the heat treatment time is 8h, and the heating rate from T1 to T2 is 2°C / min. The sample after heat treatment is a fluffy powder. The collected powder is tested for thermal storage coefficient and recorded in Table 1. An XRD test is performed, and it can be observed that there are 92% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% acetylene black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases are present;

[0147] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7 MPa, and the time is 2 h, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 8% of the acetylene black (primary particle size: 70 nm-75 nm) material in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium ferric phosphate pyrophosphate material is 77%, and the removal rate of carbon black is 100%, recorded as sample 16#;

[0148] Step 5) The prepared sample 16# was characterized by XRD, SEM, TEM and the carbon content (TG) was tested. From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.4%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 1μm-2μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 5-6nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.8wt%.

[0149] Example 17 Preparation of Na3Fe2(PO4)1P2O7

[0150] The Na3Fe2(PO4)P2O7 material was prepared by the method of Example 1, and the process and conditions were the same as those of Example 1, except that:

[0151] Step 1) 36g of ferrous oxalate dihydrate FeC2O4.2H2O, 46.8g of sodium dihydrogen phosphate dihydrate, and 18.8g of starch were weighed and added to 102g of deionized water to form a precursor solution, and 5.08g of additive raw material carbon black (primary particle size: 70nm-75nm) was added to the solution, and transferred to a sand mill with a grinding chamber of 0.3L, and the ball-to-material ratio (mass ratio) was about 8:1 (640g and 213g of zirconium dioxide balls with diameters of 4mm and 6mm were added respectively); the sand mill speed was set to 2000r / min, the time was 6h, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.6μm-0.7μm;

[0152] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 92% sodium iron phosphate pyrophosphate Na3Fe2(PO4)1P2O7 material and 8% carbon black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases exist;

[0153] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7 MPa, and the time reaches 1.8 h, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium ferric phosphate pyrophosphate material is 76%, and the removal rate of carbon black is 100%, recorded as sample 17#;

[0154] Step 5) The prepared sample 17# was characterized by XRD, SEM, TEM and the carbon content (TG) was tested. From XRD, it can be seen that the synthesized material is a pure phase sodium iron phosphate pyrophosphate Na3Fe2(PO4)P2O7 material with a purity of up to 99.5%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 1μm-2.5μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 4-5nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.6wt%.

[0155] Test Example 1

[0156] Sample 1# prepared in Example 1 was used as the positive electrode active material of the sodium ion battery, and was mixed evenly with the conductive agent acetylene black and the binder polyvinylidene fluoride at a mass ratio of 8:1:1. An appropriate amount of solvent N-methylpyrrolidone was added and mixed evenly to form a paste, which was applied on the aluminum current collector and dried and cut into discs with a diameter of 14 mm. The surface density of the active material was 1.1-3.2 mg / cm 2 (Here is 2.1 mg / cm 2 ) as the positive electrode of the battery. The negative electrode is a metal sodium sheet, the electrolyte is 1MNaClO4 / EC / DEC (EC / DEC V / V = 1:1), and the separator is a glass fiber membrane. The assembled battery is tested for charge and discharge with a voltage range of 1.8-3.6V. The discharge specific capacity under 0.2C / 1.0C / 5.0C / 10C / 50C is tested, and the discharge specific capacity under 0.2C / 50C is recorded in Table 1.

[0157] Test Example 2-17

[0158] Samples 2#-17# were tested according to the test method of Test Example 1, and the discharge specific capacity under 0.2C / 50C conditions was recorded in Table 1.

[0159] Comparative Example 1 (without adding thermal conductivity additive)

[0160] Step 1) Weigh 30.19g of iron phosphate FePO4, 18g of ferrous oxalate dihydrate FeC2O4.2H2O, 28.4g of disodium hydrogen phosphate, and 17.4g of starch, add them to 94g of deionized water to form a precursor solution, and transfer it to a sand mill with a grinding chamber of 0.3L, and add 590g and 187g of zirconium dioxide balls with diameters of 4mm and 6mm respectively according to a ball-to-material ratio (mass ratio) of about 8:1; set the sand mill speed to 2000r / min, the time to 6h, and test the particle size of the precursor slurry by a laser particle size analyzer. The particle size range is 0.8μm-0.9μm; (the upper and lower limits of the three tests are respectively taken as the average values ​​of each, the same below)

[0161] Step 2) The sand-milled precursor solution is transferred to a beaker, and then passed into a spray drying device for spray drying (inlet temperature is 170° C., outlet temperature is 100° C., feed flow rate is 50 ml / min, and compressed air pressure is 0.8 KPa) to obtain a precursor powder, wherein the particle size of the precursor powder is 30 μm-35 μm;

[0162] Step 3) The precursor powder obtained in step 2) is heat-treated in nitrogen at temperatures T1 and T2 in turn, wherein the T1 heat treatment temperature is 300°C, the heat treatment time is 3h, and the heating rate from room temperature to T1 is 5°C / min; the T2 heat treatment temperature is 500°C, the heat treatment time is 8h, and the heating rate from T1 to T2 is 2°C / min. The samples after heat treatment are fluffy powders and blocks with a certain hardness. The collected products are tested for thermal storage coefficients and recorded in Table 2; and an XRD test is performed, and it can be observed that there is 82% of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material in the powder, 12% of M-phase sodium iron phosphate NaFePO4 impurities and 6% of sodium iron pyrophosphate Na2FeP2O7 impurity phases;

[0163] Step 4) The powder obtained above was subjected to air flow pulverization using a fluidized bed jet mill with a classifying wheel (which has both air flow pulverization and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1). The experimental conditions showed that when the frequency of the classifying wheel was set to 50 Hz, the high-pressure air pressure was set to 9 MPa, and the time was 5 h, the yield was 55%, and the obtained material was recorded as sample A#;

[0164] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample A#. From XRD, it can be seen that the synthesized material contains sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of 80%, 13% of M-phase sodium iron phosphate NaFePO4 impurities and 7% of sodium iron pyrophosphate Na2FeP2O7 impurity phase. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-6μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 2 to 4nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 2.6wt%. Comparative Example 2 (outside the lower limit of the mass ratio of the thermal conductivity additive)

[0165] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Comparative Example 1, and the process and conditions were the same as those of Comparative Example 1, except that:

[0166] Step 1) 0.1 g of additive raw material carbon black (primary particle size: 70 nm-75 nm) was added to the solution at the same time, and the solution was transferred to a sand mill with a grinding chamber of 0.3 L; the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.6 μm-0.8 μm;

[0167] Step 3) The samples after heat treatment are fluffy powders and blocks with a certain hardness. The collected powders are tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 85.1% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 0.2% carbon black (primary particle size: 70nm-75nm) material in the powder, 9.83% M-phase sodium iron phosphate NaFePO4 impurity phase and 4.87% sodium iron pyrophosphate Na2FeP2O7 impurity phase material, and no other impurity phases exist;

[0168] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 9 MPa, and the time reaches 4 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 0.2% of the carbon black (primary particle size: 70 nm-75 nm) material in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 57%, and the removal rate of carbon black is 100%, recorded as sample B#;

[0169] Step 5) The prepared sample B# is characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a mixture of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material, M-phase sodium iron phosphate NaFePO4 and sodium iron pyrophosphate impurity phase Na2FeP2O7. The purity of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material is 85.3%, and there are 9.85% of M-phase sodium iron phosphate NaFePO4 impurities and 4.85% of sodium iron pyrophosphate Na2FePO4 impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-4μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 5-6nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 3.3wt%.

[0170] Comparative Example 3 (outside the upper limit of the mass ratio of high thermal conductivity materials)

[0171] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Comparative Example 1, and the process and conditions were the same as those of Comparative Example 1, except that:

[0172] Step 1) 14.1 g of additive raw material carbon black (primary particle size: 70 nm-75 nm) was added to the solution at the same time, and transferred to a sand mill with a grinding chamber of 0.3 L; the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.4 μm-0.5 μm;

[0173] Step 2) The precursor powder particle size is 25 μm-30 μm;

[0174] Step 3) The sample after heat treatment is a fluffy powder. The collected powder is tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 75% sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 25% carbon black (primary particle size: 70nm-75nm) material in the powder, and no other impurity phases exist;

[0175] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill with a classifying wheel (with both air flow pulverization and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 10 MPa, and the time reaches 5 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 25% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 45%, and the removal rate of carbon black is 100%, recorded as sample C#;

[0176] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample C#. From XRD, it can be seen that the synthesized material is pure phase sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of up to 99.8%. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 0.2μm-1μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 2-3nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.0wt%. Comparative Example 4 (Additive Particle Size 3nm-5nm)

[0177] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Comparative Example 1, and the process and conditions were the same as those of Comparative Example 1, except that:

[0178] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 3 nm-5 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.25 μm-0.4 μm;

[0179] Step 3) The samples after heat treatment are fluffy powders and blocks with a certain hardness. The collected powders are tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 86% of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% of carbon black (primary particle size: 3nm-5nm) material in the powder, 4% of M-phase sodium iron phosphate NaFePO4 impurity phase and 2% of sodium iron pyrophosphate Na2FeP2O7 impurity phase material, and no other impurity phases exist;

[0180] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill with a classifying wheel (with both air flow pulverization and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 12 MPa, and the time reaches 5 hours, there is no diffraction peak of carbon black (primary particle size: 3nm-5nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 3nm-5nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 55%, and the removal rate of carbon black is 100%, recorded as sample D#;

[0181] Step 5) The prepared sample D# is characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a mixture of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material, M-phase sodium iron phosphate NaFePO4 and sodium iron pyrophosphate impurity phase Na2FeP2O7. The purity of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material is 93.5%, and there are 4.3% of M-phase sodium iron phosphate NaFePO4 impurities and 2.2% of sodium iron pyrophosphate Na2FePO4 impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 2μm-3μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 2-3nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 3.3wt%.

[0182] Comparative Example 5 (additive particle size 300nm-310nm)

[0183] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Comparative Example 1, and the process and conditions were the same as those of Comparative Example 1, except that:

[0184] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 300 nm-310 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.75-0.95 μm;

[0185] Step 3) The samples after heat treatment are fluffy powders and blocks with a certain hardness. The collected powders are tested for heat storage coefficient and recorded in Table 1. XRD test is performed, and it can be observed that there are 84% of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material and 8% of carbon black (primary particle size: 300nm-310nm) material in the powder, 5.4% of M-phase sodium iron phosphate NaFePO4 impurity phase and 2.6% of sodium iron pyrophosphate Na2FeP2O7 impurity phase material, and no other impurity phases exist;

[0186] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill with a classifying wheel (with both air flow pulverization and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 6 MPa, and the time reaches 2 hours, there is no diffraction peak of carbon black (primary particle size: 300 nm-310 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 300 nm-310 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 80%, and the removal rate of carbon black is 100%, recorded as sample E#;

[0187] Step 5) The prepared sample E# is characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material is a mixture of sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material, M-phase sodium iron phosphate NaFePO4 and sodium iron pyrophosphate impurity phase Na2FeP2O7. The purity of the sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material is 91.3%, and there are 5.87% of M-phase sodium iron phosphate NaFePO4 impurities and 2.83% of sodium iron pyrophosphate Na2FePO4 impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 1.5μm-3μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material, with a thickness of about 4-6nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.5wt%. Comparative Example 6 (the particle size range of the precursor slurry line is 0.1-0.2μm)

[0188] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Comparative Example 1, and the process and conditions were the same as those of Comparative Example 1, except that:

[0189] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 70 nm-75 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 0.1-0.2 μm; (the average value was taken after three tests);

[0190] Step 2) The precursor powder particle size is 20 μm-25 μm;

[0191] Step 3) The samples after heat treatment are fluffy powder and blocks with a certain hardness. The collected products are tested for heat storage coefficient and recorded in Table 2; and XRD test is performed, and it can be observed that there are 85% of sodium ferric phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material in the powder, and there is also 8% of carbon black (primary particle size: 70nm-75nm), 4.67% of M-phase sodium ferric phosphate NaFePO4 impurities and 2.33% of sodium ferric pyrophosphate Na2FeP2O7 impurity phase, and no other impurity phases;

[0192] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill with a classifying wheel (with both air flow pulverization and separation functions) (manufacturer: Weifang Zhengyuan; model: LHL / Y-1), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 10 MPa, and the time reaches 5 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and the target product sodium iron phosphate pyrophosphate material yield is 57%, and the carbon black removal rate is 100%, recorded as sample F#;

[0193] Step 5) XRD, SEM, TEM characterization and carbon content (TG) test were performed on the prepared sample F#. From XRD, it can be seen that the synthesized material contains sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of 92.4%, 5% of M-phase sodium iron phosphate NaFePO4 impurities and 2.5% of sodium iron pyrophosphate Na2FeP2O7 impurity phase. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 1μm-1.5μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 2 to 4nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 3.1wt%. Comparative Example 7 (the particle size range of the precursor slurry particles is 3μm-3.5μm)

[0194] The Na4Fe3(PO4)2P2O7 material was prepared by the method of Comparative Example 1, and the process and conditions were the same as those of Comparative Example 1, except that:

[0195] Step 1) 4.68 g of additive raw material carbon black (primary particle size: 70 nm-75 nm) was added to the solution at the same time, and the particle size of the precursor slurry was tested by a laser particle size analyzer, and the particle size range was 3 μm-3.5 μm;

[0196] Step 2) The precursor powder particle size is 30 μm-35 μm;

[0197] Step 3) The samples after heat treatment are fluffy powder and blocks with a certain hardness. The collected products are tested for heat storage coefficient and recorded in Table 2; and XRD test is performed, and it can be observed that there are 81% of sodium ferric phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material in the powder, 8% of carbon black (primary particle size: 70nm-75nm), 7.33% of M-phase sodium ferric phosphate NaFePO4 impurities and 3.67% of sodium ferric pyrophosphate Na2FeP2O7 impurity phase, and no other impurity phases;

[0198] Step 4) The powder obtained above is subjected to air flow pulverization using a fluidized bed air flow mill (manufacturer: Weifang Zhengyuan; model: LHL / Y-1) with a classifying wheel (having both air flow pulverization and separation functions), and a sampling inspection is performed at intervals of 10 minutes using XRD detection technology to detect the XRD diffraction peak of the thermal conductive additive in the material collected after air flow pulverization, and the parameters of the air flow pulverization device are adjusted based on this. The experimental conditions show that when the frequency of the classifying wheel is set to 50 Hz, the high-pressure air pressure is set to 7.5 MPa, and the time reaches 3 hours, there is no diffraction peak of carbon black (primary particle size: 70 nm-75 nm) in the material obtained by air flow pulverization, that is, 8% of the carbon black (primary particle size: 70 nm-75 nm) in step 3) can be effectively removed by the air flow pulverization separation process in step 4), and at this time, the yield of the target product sodium iron phosphate pyrophosphate material is 75%, and the removal rate of carbon black is 100%, recorded as sample G#;

[0199] Step 5) The prepared sample G# is characterized by XRD, SEM, TEM and tested for carbon content (TG). From XRD, it can be seen that the synthesized material contains sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 material with a purity of 88%, and there are 7.97% M-phase sodium iron phosphate NaFePO4 impurities and 4.03% sodium iron pyrophosphate Na2FeP2O7 impurity phases. From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-5μm. From TEM, it can be seen that there is an amorphous carbon layer coating on the outer surface of the material with a thickness of about 5-6nm. TG shows that the amorphous carbon content coated on the outer surface of the material is 4.5wt%.

[0200] Comparative test example 1

[0201] Sample A# prepared in Comparative Example 1 was used as the positive active material material of the sodium ion battery, and was mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 8:1:1, and an appropriate amount of solvent N-methylpyrrolidone was added to form a paste after mixing and applied to the aluminum current collector. After drying, it was cut into a disc with a diameter of 14 mm, and the active material surface density was 1.1-3.2 mg / cm2 (here 2.1 mg / cm2), which was used as the positive electrode of the battery. The negative electrode was selected from a metal sodium sheet, the electrolyte was selected from 1MNaClO4 / EC / DEC (EC / DEC V / V = 1:1), and the diaphragm was selected from a glass fiber membrane. The assembled battery was subjected to charge and discharge tests with a voltage range of 1.8-3.6V, and the discharge specific capacity under the conditions of 0.2C / 1.0C / 5.0C / 10C / 50C was tested, and the discharge specific capacity under the conditions of 0.2C / 50C was recorded in Table 2.

[0202] Comparative test example 2-7

[0203] Samples B#-G# were tested according to the test method of Comparative Test Example 1, and the discharge specific capacities under 0.2C / 50C conditions were recorded in Table 2.

[0204] Table 1 Test data of discharge specific capacity of materials in the embodiment

[0205]

[0206] Table 2 Comparative material discharge capacity test data

[0207]

[0208] in conclusion

[0209] The patent of the present invention is to improve the heat transfer in the heat treatment process, reduce heat accumulation, and prevent the target product from generating impurities after heat accumulation, which affects the purity and performance of the material by adding thermal conductivity additives to the raw materials. During the heat treatment process, the crystals gradually form phases from the inside to the outside, and the internal crystal nuclei should have a high heat transfer coefficient. On the one hand, in order to prevent the appearance of impurities due to the influence of heat accumulation, it is necessary to transfer the heat to the external unreacted precursor raw materials in time to make them form phases. Only when the above requirements are met can the uniformity of heat distribution in the heat treatment process be improved. The thermal conductivity additive can be selected from one or more of acetylene black, carbon black, Ketjen black, graphite, carbon nanotubes, carbon fibers, and graphene. It can improve the heat transfer of the material, reduce heat storage during the heat treatment process, and realize the preparation of high-purity and high-performance materials. The heat accumulation process can be quantitatively expressed as the heat storage coefficient of the product (as shown in Tables 1 and 2), and the heat storage coefficient is relatively high. The heat transfer process of the material is slow during the heat treatment process, the heat accumulation is serious, the product is decomposed by heat to produce impurities, resulting in a decrease in electrochemical performance; experiments show that even when the mass of the precursor is increased, phosphate and fluorophosphate polyanionic materials with high purity, high specific capacity and high rate performance can still be prepared, which greatly promotes the development and application of such materials in the field of energy storage (for example, the purity of the sodium iron phosphate pyrophosphate material prepared in Example 1 is as high as 99.2%, and the XRD diffraction spectrum shows that the added thermal conductivity additive carbon black can be effectively removed with a yield of 78%, the particle size after airflow crushing is 1μm-2μm, and the specific capacity of the material under 0.2C is 125mAh.g -1 The specific capacity of the material under 50C conditions is 90 mAh.g -1 ;

[0210] The thermal conductive additives selected in the present invention, such as acetylene black, carbon black, ketjen black, graphite, carbon nanotubes, carbon fiber, graphene and other carbon materials, all have good electrical and thermal conductivity, and their mass ratio with the precursor also has a certain optimization relationship. When the mass ratio with the precursor is too low (<0.5%), the thermal storage coefficient of the product is high (180-200W / (m 2 / k)), it is impossible to ensure the rapid transfer of heat during the sintering process, resulting in heat accumulation, resulting in a decrease in product purity and electrochemical performance. When the mass ratio of the precursor is too high (>10%), the lower heat storage coefficient (103W / (m 2 / k)) can effectively promote the uniformity of heat distribution during the heat treatment process and prepare high-purity and high-specific capacity materials. However, the use of excessive thermal conductive additives makes the parameters of airflow pulverization in the removal process more stringent, requiring a longer pulverization time and higher air pressure. Under long-term and high-pressure conditions, the product performance will be reduced, the carbon content of the product surface will be reduced, resulting in uneven carbon coating of the product and reduced yield of the target product, thereby affecting the performance of the product and not conducive to the large-scale utilization of the material. Through experimental verification and optimization, it can be found that when the mass ratio of the thermal conductive additive to the precursor is 0.5% to 10%, the thermal conductive additive can be effectively removed, and the prepared material has excellent electrochemical properties and a high yield. For example, in Examples 1 to 7, the prepared sodium iron phosphate pyrophosphate material has a purity of up to 95%-99.9%, and the XRD diffraction spectrum shows that the added carbon black can be effectively removed. The particle size is 0..5μm-3.5μm, and the specific capacity of the material under 0.2C is 115-125mAh.g -1 The specific capacity of the material under 50C condition is 75~90mAh.g -1 , heat storage coefficient is (100-150W / (m 2 / k)), the yield is 60% to 85%, and the best mass ratio of the precursor is 4% to 6%, as in Examples 1, 4, and 5, the purity of the sodium iron pyrophosphate material is 99.2% to 99.7%, and the thermal storage coefficient is (105-116W / (m 2 / k)), which can realize the rapid transfer of heat. The specific capacity of the material under 0.2C condition is 122-125mAh.g -1 The specific capacity of the material under 50C conditions is 84-90 mAh.g -1 , the yield is 76.5% to 78.5%; when the mass ratio of the precursor is less than 0.5% or even not added, as in Comparative Examples 1 to 2, the product is sintered unevenly after the heat treatment process (the heat storage coefficient is 180-200W / (m 2 / k)) showed different degrees of agglomeration, and the purity (82% to 85.3%) and electrochemical performance of the product were reduced. The XRD diffraction spectrum showed that the added carbon black could be removed, but the prepared sodium iron phosphate pyrophosphate material contained M-phase sodium iron phosphate impurities and sodium iron pyrophosphate impurity phases, which were thermal decomposition products produced by uneven heating. Since there were blocks of a certain hardness in the product, the air flow crushing process required a long pressure and time to ensure the particle size requirements of the final material, so the yield was also reduced to only 55%-57%. The long-term high-pressure crushing further reduced the performance of the material. The specific capacity of the material under 0.2C was 95 to 100 mAh.g -1 The specific capacity of the material under 50C condition is 50~55mAh.g -1When the mass ratio of the precursor is greater than 10%, as in Comparative Example 3, the heat distribution uniformity during heat treatment is high (the heat storage coefficient is 103W / (m 2 / k)), although it will not form agglomerates, the XRD diffraction spectrum shows that the added carbon black can be effectively removed. During the removal process, the yield before and after airflow crushing is low, only 45%, which is not conducive to practical application. In addition, after excessive airflow crushing, the material's electrochemical properties are affected due to continuous contact and collision during the process. The specific capacity of the material under 0.2C conditions is only 110mAh.g -1 The specific capacity of the material under 50C condition is 68 mAh.g -1 .

[0211] Similarly, under other optimized conditions, the particle size of the precursor slurry and the particle size of the thermal conductive additive will affect the performance, purity, yield and other parameters of the final material. For example, in Examples 8-11, experimental verification shows that when the particle size of the thermal conductive additive meets a certain range (10nm-200nm), it can achieve good contact and coverage with the precursor slurry particles and does not agglomerate itself, fully exerting the task of heat transfer during the heat treatment process, and the heat storage coefficient is 90-122W / (m 2 / k), the yield before and after airflow crushing is 60%-82%, the material purity is 98.4%-99.1%, and the specific capacity of the material under 0.2C condition is 111-114mAh.g -1 The specific capacity of the material under 50C conditions is 78-81 mAh.g -1 When the particle size of the thermal conductive additive is low (<10nm), the surface energy is high and it is easy to agglomerate, and it cannot achieve good contact with the precursor particles and cannot achieve rapid heat transfer during the heat treatment process, and thermal decomposition impurities begin to appear, and the subsequent removal process yield is low. When the particle size is high (>200nm), it will not agglomerate itself, but it is also impossible to achieve a high coverage rate, and thermal decomposition impurities will also be produced in the product. The above effects will cause the material performance to decline or have an adverse effect on other process parameters. For example, in Comparative Examples 4-5, the purity of the sodium iron pyrophosphate material is 91.3%-93.5%, and the thermal storage coefficient is (120-125W / (m 2 / k)), the specific capacity of the material under 0.2C condition is 105-108mAh.g -1 The specific capacity of the material under 50C conditions is 60-63 mAh.g -1, the yield is 55% - 80%. The particle size of the precursor slurry will also affect the above process. When there are other insoluble particulate matters in the precursor slurry besides the additive raw materials, when the linear average diameter range of the particles in the precursor slurry is 0.1μm - 1.5μm, good contact and coating are achieved between the precursor slurry particles and the thermal conductivity additive, the heat distribution is uniform during the heat treatment process, the prepared material has a high purity, and it is beneficial to the subsequent processing process. For example, in Examples 12 - 13, the purity of the sodium iron pyrophosphate phosphate material is 97.8% - 99%, and the heat storage coefficient is (105 - 120W / (m 2 / k)), and rapid heat transfer can be achieved. The specific capacity of the material under the condition of 0.2C is 108 - 113mAh.g -1 , and the specific capacity of the material under the condition of 50C is 75 - 78mAh.g -1 , the yield is 62% - 79%. When the particle size of the particles in the precursor slurry is small, the particles are prone to agglomeration, or when the particle size is large, uniform coating with the thermal conductivity additive cannot be achieved, which will affect the uniformity of the heat distribution during the above heat treatment process and thus affect the material properties. For example, in Comparative Examples 6 - 7, the purity of the sodium iron pyrophosphate phosphate material is 88% - 92.4%, and the heat storage coefficient is (120 - 130W / (m 2 / k)), and the specific capacity of the material under the condition of 0.2C is 94 - 103mAh.g -1 , and the specific capacity of the material under the condition of 50C is 47 - 57mAh.g -1 , the yield is 57% - 75%.

[0212] Although the introduction of the thermal conductivity additive can improve the uniformity of the heat distribution during the heat treatment process, the heat treatment temperature should be selected within a suitable range. It can be seen from the examples of this invention patent that when the heat treatment temperature T2 in this patent satisfies 400℃ < T1 ≤ 650℃, sodium iron pyrophosphate phosphate materials with excellent performance can be prepared. The introduction of the thermal conductivity additive can broaden the temperature tolerance range of this material, and materials with excellent electrochemical performance can be prepared within the above range. For example, in Examples 14 - 15, the purity of the sodium iron pyrophosphate phosphate material is 95.7% - 99.5%, and the heat storage coefficient is (115 - 119W / (m 2 / k)), and the specific capacity of the material under the condition of 0.2C is 110 - 112mAh.g -1 , and the specific capacity of the material under the condition of 50C is 70 - 76mAh.g -1 , the yield is 74% - 78%.

[0213] At the same time, other process parameters in the material preparation process will also affect the performance of the final target product, but the correlation coefficient of the invention point of this patent is low. Therefore, the parameters are adjusted through experimental design to make them at a more optimized level: such as: the solid content of the precursor in the early mixing process, the inlet and outlet temperature of spray drying, the particle size of the precursor powder collected before and after spraying, etc., are all at a level with a low degree of influence on the experimental results.

[0214] In summary, the implementation method involved in the present invention can also prepare materials with excellent electrochemical properties when the thermal conductive additive is acetylene black, and is also suitable for application in other phosphate-based sodium ion battery positive electrode materials (sodium phosphate Na3Fe2(PO4)1P2O7). For example, in Examples 16 and 17, the heat distribution uniformity of the heat treatment is high (the heat storage coefficient is 111-112W / (m 2 / k)), the XRD diffraction spectrum shows that the added carbon black is effectively removed, the purity of the target material is 99.4%-99.5%, the yield is 76%-77%, and the specific capacity of the material under 0.2C condition is 116-124mAh.g -1 The specific capacity of the material under 50C conditions is 85-88 mAh.g -1 .

Claims

1. Preparation method of iron-based phosphate or fluorophosphate polyanionic compounds, characterized in that, The compound has one or more than two of the structures shown in the following iron-based phosphate polyanionic compound formula I, formula II, formula III, formula IV, or fluorophosphate polyanionic compound formula V, or formula VI: Na4Fe3(PO4)2P2O7, formula I; Na3Fe2(PO4)1P2O7, formula II; NaFePO4, formula III; Na2FeP2O7, formula IV; Or the iron-based fluorophosphate polyanionic compound has the structure shown in formula V and / or VI: Na2FePO4F, formula V; Na5Fe2(PO4)2F3, formula VI; The preparation method of the polyanionic compound shown in formula I, formula II, formula III, formula IV, V or VI includes: Step 1, mixing a carbon source, a sodium source, an iron source, a phosphorus source, and an additive raw material evenly in a solvent to obtain a precursor slurry, or mixing a carbon source, a sodium source, an iron source, a phosphorus source, a fluorine source, and an additive raw material evenly in a solvent to obtain a precursor slurry, and drying to obtain a precursor powder; The additive raw material is one or more than two of acetylene black, carbon black, Ketjen black, graphite, carbon nanotubes, carbon fibers, graphene; the added mass M1 of the additive raw material is 0.5% - 10% of the total mass of the compound material synthesis raw materials in step 1 (the compound material synthesis raw materials include the sum of the masses of the added carbon source, sodium source, iron source, and phosphorus source, or the compound material synthesis raw materials include the sum of the masses of the added carbon source, sodium source, iron source, phosphorus source, and fluorine source); more preferably 4% - 6%; The particle size range of the precursor slurry is 0.3μm - 1.5μm; Step 2, heat-treating the precursor powder obtained in step 1 in an inert atmosphere or an inert atmosphere containing H2, and after heat-treatment, the product M2 of the iron-based phosphate or fluorophosphate polyanionic compound can be obtained; The heat-treatment atmosphere is selected from an inert atmosphere or an inert atmosphere with H2 reducibility, the molar content of H2 in the heat-treatment atmosphere is 0 - 50%, preferably 10% - 20%; the heat-treatment includes the process of treating at the first temperature T1 in sequence and the process of treating at the second temperature T2 after treating at the first temperature T1; the temperature T1 is 200 ≤ T1 ≤ 400°C, the treatment time is 0.5 - 6h; the temperature T2 is 400°C < T1 ≤ 650°C, the treatment time is 3 - 20h; the difference between T2 and T1 is greater than or equal to 50°C; Step 3, removing the additive raw material added in step 1 from the product obtained in step 2 by a jet mill to obtain the final product M3 of the iron-based phosphate or fluorophosphate polyanionic compound, the particle size range of the final product is 0.2μm - 5μm, preferably in the range of 1.5μm - 3.5μm, and the yield before and after jet milling (the yield is defined as: the mass of the final product powder material obtained after jet milling is the ratio of the mass of the substance except the additive raw material added in step 1 in the product obtained after heat-treatment in step 2, that is, M3 / (M2 - M1)) is 60% - 85%, preferably in the range of 75% - 80%; The iron-based phosphate polyanionic compound is a carbon-coated iron-based phosphate polyanionic compound material, and the amount of the carbon source added should ensure that the mass content of the phosphate or fluorophosphate polyanionic compound carbon after airflow grinding is 3wt% to 10wt%, and more preferably 4wt% to 5wt%.

2. The method according to claim 1, characterized in that: In step 1, when the additive raw material contains acetylene black, carbon black, Ketjen black or graphite, the particle size thereof is 10 nm-200 nm, more preferably 50-100 nm; When the additive raw material contains carbon nanotubes or carbon fibers, the diameter thereof is distributed in the range of 2nm-20nm, more preferably 5-10nm; When the additive raw material contains graphene, its thickness is 0.3nm-3.5nm, more preferably 1-2nm; In step 1, there are no other insoluble particles in the uniformly mixed precursor slurry except the additive raw materials (that is, the added carbon source, sodium source, iron source, and phosphorus source are all soluble compounds, or the added carbon source, sodium source, iron source, phosphorus source, and fluorine source are all soluble compounds), or there are other insoluble particles in the uniformly mixed precursor slurry except the additive raw materials; In step 2, the inert atmosphere gas includes at least one or more of argon, helium, and nitrogen.

3. The method according to claim 1, characterized in that: In step 1, the sodium source, iron source, phosphorus source, and additive raw materials are uniformly mixed in a solvent by at least one or more of ball milling, pot milling, sand milling, etc.; the solvent is water, ethanol, or a mixed solvent of water and ethanol, and the solid content of the precursor solution is 30wt% to 75wt%, more preferably 45wt% to 55wt%: The sand milling process requires the addition of a sand milling medium, the sand milling speed is 2000-5000 r / min, and the sand milling time is 0.5-8 h; the sand milling medium is one or more of natural sand beads, glass beads, steel beads, zirconium oxide beads, zirconium silicate beads, and agate beads; the ball-to-material ratio (mass ratio of balls (medium) to solid materials (other substances except solvents)) is (1-10); the diameter of the sand milling medium is 0.2-1 cm, and is preferably composed of 0.4 cm and 0.6 cm in diameter according to a mass ratio of (3-3.5):1; The ball mill needs to add ball milling media, the rotation speed of the ball mill is 200-800r / min, and the ball milling treatment time is 3-15h; the ball milling media is one or more of zirconium oxide beads, agate beads, zirconium silicate beads, etc.; the ball-to-material ratio (mass ratio of balls (medium) to solid materials (other substances except solvent)) is (1.5-7); the diameter of the ball milling media is 2-12cm, preferably composed of diameters of 6cm, 4cm, and 2cm in a mass ratio of 1: (2-2.5): (2-2.5); The pot mill needs to be added with pot mill media. The rotation speed of the pot mill in step 1 is 20-40 r / min, and the pot mill treatment time is 20h-72h. The pot mill medium is one or more of zirconium oxide beads, agate beads, and zirconium silicate beads; the ball-to-material ratio (mass ratio of balls (medium) to solid materials (other substances except solvent)) is (1.1-3); the diameter of the pot mill medium is 4-12 cm, preferably a combination of 6 cm and 4 cm in diameter according to a mass ratio of (2-2.5):1; The solvent is water, ethanol, or a mixed solvent of water and ethanol. The mass of water in the mixed solvent preferably accounts for (30-80) wt%, more preferably (45-55) wt%, and the mass of ethanol preferably accounts for (20-70) wt%, more preferably (45-55) wt%.

4. The method according to claim 1, characterized in that: The drying method in step 1 is preferably spray drying. Preferably, the feed flow rate is controlled to be 20mL / min~60mL / min, the inlet air temperature is controlled to be 120℃~195℃, the exhaust port temperature is 80℃~110℃, the compressed air pressure is 0.03KPa~0.9KPa, and the precursor slurry is pumped into the spray dryer atomizer through a peristaltic pump to collect the powder; after the precursor slurry is dried, a precursor powder with a particle size of 20μm-30μm is obtained.

5. The method according to claim 1, characterized in that: The air flow mill described in step 3 is a fluidized bed air flow mill (with a turbine classifier), a circulating tubular air flow mill (with an inertial classifier) ​​or a jet air flow mill (with a classifying wheel belt). The compressed air pressure is 4 to 12 MPa. Sampling inspection is carried out every 1-20 minutes (preferably 5-15 minutes) to detect whether the additive raw materials are present in the materials collected after air flow milling. The inspection time when the additive raw materials are just completely removed is the air flow milling time. Usually, the air flow milling time is 1h-5h.

6. The method according to claim 1, characterized in that: 1) The iron source is selected from one or more of iron powder, ferrosinite, ferrous oxide, ferrous oxalate, ferrous oxalate (dihydrate), ferric phosphate, ferric pyrophosphate, ferrous citrate, ferric nitrate, ferrous nitrate, ferrous sulfate, ferrous sulfate, ferrous chloride, ferrous chloride, ferrous acetate, ammonium ferrous sulfate, ferric citrate, ammonium ferric citrate, and sodium ferric citrate succinate; 2) The sodium source is at least one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium phosphate, sodium pyrophosphate, sodium hydrogen pyrophosphate, sodium hydrogen phosphate, sodium dihydrogen phosphate, sodium citrate, sodium oxalate, sodium nitrate, sodium tartrate, sodium ascorbate, sodium gluconate, sodium glutamate, and sodium formate; 3) The phosphorus source is at least one or two or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid, ammonium dihydrogen phosphate, triammonium phosphate, pyrophosphoric acid, sodium pyrophosphate, sodium dihydrogen pyrophosphate, and ammonium dihydrogen pyrophosphate; 4) The carbon source is selected from at least one or more of starch, carboxymethyl starch, sodium carboxymethyl starch, sodium alginate, citric acid, oxalic acid, ammonium citrate, ascorbic acid, formaldehyde, acetaldehyde, lactic acid, malic acid, glucose, sucrose, maltose, and maltodextrin; 5) The fluorine source is selected from at least one or more of sodium fluoride, ammonium fluoride, polyvinylidene fluoride, polyperfluoroethylene, and hydrofluoric acid.

7. The preparation method according to claim 1 or 6, characterized in that: Preferably, the phosphate polyanionic compound has a structure as shown in formula I, and in the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 4:3:4, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively; Preferably, the phosphate polyanionic compound has a structure as shown in Formula II. In the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 3:2:3, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively; Preferably, the polyanionic compound has a structure as shown in Formula III, and in the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 1:1:1, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively; Preferably, the polyanionic compound has a structure as shown in Formula IV. In the slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is 2:1:2, and the molar ratio of the sodium source, the iron source, and the phosphorus source is calculated based on the molar amount of the sodium element, the iron element, and the phosphorus element, respectively; Preferably, the polyanionic compound has a structure shown in Formula V. In the slurry, the molar ratio of the sodium source, the iron source, the phosphorus source, and the fluorine source is 2:1:1:1, and the molar ratio of the sodium source, the iron source, the phosphorus source, and the fluorine source is based on the molar amount of the sodium element, the iron element, the phosphorus element, and the fluorine element, respectively; Preferably, the polyanionic compound has a structure as shown in VI. In the slurry, the molar ratio of the sodium source, iron source, phosphorus source and fluorine source is 5:2:2:3, and the molar ratio of the sodium source, iron source, phosphorus source and fluorine source is based on the molar amount of the sodium element, iron element, phosphorus element and fluorine element, respectively.

8. An iron-based phosphate or fluorophosphate polyanionic compound prepared by the preparation method according to any one of claims 1 to 7.

9. Use of one or more of the iron-based phosphate or fluorophosphate polyanionic compounds prepared by the preparation method according to any one of claims 1 to 7 or one or more of the iron-based phosphate or fluorophosphate polyanionic compounds according to claim 8 in a sodium ion battery, characterized in that: One or more of the iron-based phosphate or fluorophosphate polyanion compounds are used as active materials for positive electrode materials of sodium ion batteries.

10. A positive electrode material for a sodium ion battery, characterized in that: The positive electrode material contains one or more of the iron-based phosphate or fluorophosphate polyanionic compounds prepared by the preparation method according to any one of claims 1 to 8, or contains one or more of the iron-based phosphate or fluorophosphate polyanionic compounds according to claim 8; In the positive electrode material, the content of the iron-based phosphate or fluorophosphate polyanionic compound is (60-98) wt%; The positive electrode material further contains a conductive agent and a binder, wherein the mass ratio of the iron-based phosphate or fluorophosphate polyanionic compound, the conductive agent and the binder is (60-98) wt%: (1-39) wt%: (1-39) wt%; The conductive agent is at least one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene; The binder is polyvinylidene fluoride: at least one or more of PVDF5130, HSV900 and kynar761A.

Citation Information

Patent Citations

  • Rapid microwave reaction preparation method of ternary polyanionic phosphate / carbon cathode material for power lithium ion battery

    CN103996823A

  • Method for preparing Na4Fe3 (PO4) 2 (P2O7) by homogeneous phase method and application

    CN113060713A

  • Positive electrode material and preparation method thereof

    CN115621460A

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN115986080A

  • Preparation method of fluorophosphate-based polyanionic compound and application of fluorophosphate-based polyanionic compound in sodium-ion battery

    CN116265388A